Heritability and Genetic Relationships for Drought‐Related Traits in Peanut. Issue 4 (1st July 2013) - Chen, Charles Y.; Nuti, Russell C.; Rowland, Diane L.; Faircloth, Wilson H.; Lamb, Marshall C.; Harvey, Ernest
ABSTRACT: Water‐use efficiency is often genetically correlated with specific leaf area (SLA) and leaf C isotopic composition (δ 13 C) in peanut ( Arachis hypogaea L.). The objectives of this study were to examine the effects of environment, genotype, and genotype × environment interaction on SLA, δ 13 C, harvest index (HI), and yield and to estimate heritability and the genetic relationships. Fifteen genotypes were tested at two locations with different drought intensities for 2 yr. The additive main effects and multiplicative interaction analysis based on yield data divided eight environments (locations × treatments × years) into four clusters, which reflected a gradient in drought stress, indicating yield trait is a good indication of drought stress. The genotype Exp8‐12 was identified as a best drought tolerant germplasm across environments. Heritability estimates for HI (0.68 to 0.89) and δ 13 C (0.75 to 0.89) were higher than those for SLA (0.31 to 0.88) and yield (0.12 to 0.65). A positive but small genetic correlation coefficient ( r g ) (0.26) was found between HI and yield, and low to moderate r g (0.14 to 0.55) were observed between HI and SLA. A relative high negative genetic correlation r g (−0.81 to −0.57) was found between δ 13 C and yield. In theory, the high heritability and no G×E interaction for δ 13 C make it possible a surrogate that can be used to assess drought tolerance in peanut breeding.